M08 Laquinimod Reduces Neuronal Caspase-6 Activation And Axonal Degeneration In Vitro. (17th September 2014) - Ladha, S; Ehrnhoefer, DE; Tsang, M; Qiu, X; Hayden, MR
Abstract : Background: Laquinimod is an immunomodulatory compound that reduces relapse rate, brain atrophy and disability progression in multiple sclerosis. It has well-documented effects on inflammation, is widely distributed in the CNS and has been shown to ameliorate axonal damage in vitro and in vivo through an unknown mechanism. We have shown recently that caspase-6 is an important mediator in axonal degeneration, since sympathetic neurons derived from caspase-6 -/- mice do not degenerate when cultured in the absence of neuronal growth factor (NGF). We therefore investigated whether the beneficial effect of Laquinimod on axonal damage is mediated by caspase-6. Aim: To investigate neuron-specific beneficial effects of Laquinimod. Methods: Cell-free and cell-based enzymatic activity assays were used to determine whether Laquinimod directly inhibits caspase-6. To investigate an effect on intraneuronal caspase-6 activity, primary cortical neurons were treated with camptothecin in the presence or absence of Laquinimod, and cleavage of the caspase-6 specific substrate lamin A was quantified by ELISA. Axonal degeneration of primary sympathetic neurons from the superior cerebral ganglion was induced by NGF withdrawal in the presence or absence of Laquinimod. Results: Laquinimod did not directly inhibit caspase-6 activity in cell-free or transfection-based cellular systems. However, the presence of Laquinimod in camptothecin-stressed primary cortical neuron cultures led to a significant decrease in caspase-6 activation. In cultures of primary superior cerebral ganglion neurons, Laquinimod partially protected axons from degeneration after NGF withdrawal, a process that is specifically dependent on caspase-6 activity, in agreement with the reduction of caspase-6 activity observed in stressed cortical neurons. Conclusions: The beneficial effects of Laquinimod described so far involve neuroprotection through the downregulation of glial activation, whereas our findings represent a novel, purely neuronal mechanism of action for this drug. We propose that by preventing neuronal caspase-6 activation and axonal degeneration, Laquinimod might also provide benefits in other neurodegenerative disorders such as Huntington's disease that are associated with excessive activation of caspase-6.